ARE WOMEN DOGS? : The Reality of Racism in Indonesia Reviewed from Matthew 15:21-28 - Tanasyah, Yusak (QUAERENS: Journal of Theology and Christianity Studies, 2025)
This study explores the theme of discrimination based on ethnicity and religion as reflected in Matthew 15:21-28, particularly in the Indonesian context. The background to the problem lies in the persistent social issues surrounding discrimination in various forms, which can be seen as a reflection of deeper cultural and theological gaps. The purpose of this study is to analyze the text of Matthew 15: 21-28 in relation to contemporary discrimination issues and to obtain messages that can contribute to the promotion of inclusiveness and understanding in Indonesian society. This study uses the method of textual analysis of the scriptures along with socio-cultural examination of the current landscape in Indonesia. Through this approach, the study identifies key themes and insights in biblical narratives that resonate with the modern experience of marginalized groups. The results show that the section challenges prevailing attitudes towards discrimination and calls for a reevaluation of social norms. It highlights the importance of compassion and the recognition of shared humanity, offering a theological foundation for overcoming discrimination.